The Role of Mandibular Thickness in Determining Anteroposterior Skeletal Relationships - Akihiro Tsuboi; So Koizumi; Masahiro Takahashi; Yu Hikita; Tetsutaro Yamaguchi (Dentistry Journal)
Objectives: This study aimed to explore the association between the ANB angle and mandibular bone thickness in individuals with skeletal malocclusion. Methods: We analyzed 224 adults, with a gender imbalance noted (68 men and 156 women), and an age range between 18.0 and 65.1 years. The thicknesses of the ramus (RT) and the body of the mandible (BT) were measured at 25 sites on each side (left and right) of the jaw, using CT images. The main focus was on the statistical associations between the ANB angle and the ratio (BT-RT)/volume of the mandible (V). Results: Results revealed a significant negative association between (BT-RT)/V and the ANB angle (p < 0.001), while a positive association was found for RT/V (p < 0.001). No significant association emerged for BT/V. Conclusions: The findings indicated that with increased mandibular protrusion, the ramus thickness decreased, whereas the body thickness remained unchanged. The differing relationships in mandibular thickness underscore the significance of CT imaging in predicting craniofacial growth patterns, particularly in observing discrepancies between the mandibular body and ramus as they relate to the anterior–posterior jaw relationship.